Ultrafast treatment method and application of surface microstructure of large-size membrane electrode

By performing ultra-fast treatment on large-sized film electrodes, the crystallinity of manganese dioxide and the conductivity are reduced, the shortcomings in the oxygen reduction reaction activity and reaction kinetics of existing film electrodes are solved, and efficient catalytic performance and long-term voltage stability are achieved.

CN119542626APending Publication Date: 2025-02-28HAINAN GREEN RAN NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795276.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The membrane electrodes of existing metal air batteries show lower efficiency in oxygen reduction reaction (ORR) activity and reaction kinetics, especially membrane electrodes with manganese dioxide as the main catalyst. The high crystallinity structure leads to fewer active sites and poor conductivity, limiting the efficiency of electrochemical reactions.

Method used

An ultrafast treatment method using a microstructure of the surface of large-size membrane electrodes, including removing moisture and ethanol in a vacuum drying box, followed by multiple treatments in a plasma instrument to reduce the crystallinity of manganese dioxide, expose more active sites and improve conductivity.

Benefits of technology

By systematically controlling the process parameters of the plasma instrument, the membrane electrode was modified, which significantly improved the catalytic performance. The power density of the alkaline aluminum air battery reached 110mWcm-2 comparable to Pt/C, and the modified membrane electrode maintained a high voltage stability during long-term discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542626A_ABST
    Figure CN119542626A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrafast treatment technology and application of a surface microstructure of a large-size membrane electrode, and solves the problems of slow dynamics and insufficient activity of a membrane electrode of a metal-air battery. The membrane electrode firstly passes through a vacuum drying box to remove water and ethanol in the membrane electrode, and then the membrane electrode is put into a plasma treatment instrument into which nitrogen atmosphere is introduced to be treated for four times, so that the air electrode for the metal air battery can be obtained. According to the method, the membrane electrode is subjected to ultrafast treatment through a plasma instrument, the treatment acts on a main oxygen reduction catalyst manganese dioxide in the membrane electrode, the crystallinity of the manganese dioxide is reduced through treatment of the plasma instrument, a large number of ion diffusion channels and grain boundaries appear on the boundary of the manganese dioxide, and the conductivity of the manganese dioxide is improved; and more active sites are exposed. And the catalytic performance of the membrane electrode is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microscopic modification of metal-air battery membrane electrodes, and in particular relates to an ultrafast processing method and application of the surface microstructure of a large-size membrane electrode. Background Art

[0002] The ever-increasing demand for energy has prompted humans to develop sustainable energy technologies. As a new type of power source, metal-air batteries have many advantages such as high energy density, low cost, no pollution, and high safety, and have been favored by researchers at home and abroad. In industry, manganese dioxide, carbon nanotubes, conductive carbon, activated carbon, PTFE, and ethanol are usually rolled to obtain a catalytic membrane. The catalytic membrane, waterproof and breathable membrane, current collector, and waterproof and breathable membrane are stacked in order, and then the membrane electrode is obtained through a membrane laminating machine. The performance of metal-air batteries mainly depends on the ORR (oxygen reduction) performance of the membrane electrode.

[0003] However, the performance of metal-air batteries depends largely on the oxygen reduction reaction (ORR) activity of the membrane electrode, which currently still has a bottleneck. Membrane electrodes with manganese dioxide as the main catalyst show defects of low ORR activity and reaction kinetics in practical applications. Although the high crystallinity structure of manganese dioxide is stable, it has fewer active sites and poor conductivity, which seriously limit the efficiency of the electrochemical reaction. Although other high-efficiency catalysts (such as Pt / C) can partially solve these problems, their cost is too high and they are not suitable for large-scale industrial applications.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide an ultrafast processing method and application of the surface microstructure of a large-size membrane electrode, and solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0007] An ultrafast processing method for the surface microstructure of a large-scale membrane electrode comprises the following steps:

[0008] S1: Place the membrane electrode in a vacuum drying oven to remove moisture and ethanol inside the membrane electrode;

[0009] S2: self-cleaning in a plasma apparatus with a nitrogen atmosphere until the gas introduced into the chamber is entirely nitrogen;

[0010] S3: placing the membrane electrode into a plasma treatment apparatus with a nitrogen atmosphere for multiple treatments to obtain a treated membrane electrode.

[0011] Optionally, the vacuum drying oven in S1 has a vacuum degree of -1 to -3 MPa, a temperature of 60 to 80° C., and a drying time of 8 to 12 hours.

[0012] Optionally, the membrane electrode used in step S1 is a MnO2 membrane electrode.

[0013] Optionally, the cleaning power during self-cleaning in step S2 is 200 W, each cleaning time is 180 seconds, and the number of cleaning times is 3 times.

[0014] Optionally, in step S3, when a plasma treatment apparatus is used for treatment, the treatment power is 200 W, each treatment time is 15 to 30 minutes, the treatment time is 15-30 minutes, and the number of treatments is 4 times.

[0015] Optionally, after each treatment in step S3, the membrane electrode needs to be rotated 90° before the next treatment.

[0016] A membrane electrode is obtained after being processed by the method.

[0017] A membrane electrode is used as a positive electrode of an aluminum-air battery or a zinc-air battery.

[0018] The negative electrode of an aluminum-air battery or a zinc-air battery is an aluminum plate or a zinc plate, and the electrolyte is a 4M KOH solution.

[0019] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:

[0020] 1. The present invention modifies industrial large-size membrane electrodes by systematically regulating process parameters such as power, working time and working times of a plasma instrument, resulting in a decrease in the crystallinity of manganese dioxide in the membrane electrode, revealing more crystal faces and ion channels, thereby exposing more active sites and improving the conductivity of the catalyst.

[0021] 2. The membrane electrode modified by the plasma instrument has excellent catalytic performance, and the power density of the alkaline aluminum-air battery reaches 110mWcm -2 Comparable to Pt / C at 5 mA cm -2 The modified membrane electrode was discharged in a cross-current state at a current density of , and the average voltage was about 1.4V after working for 180 hours.

[0022] 3. Compared with modified catalysts, directly modifying large-size membrane electrodes can simplify the process, improve production efficiency and reduce production costs.

[0023] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0025] Figure 1 The characterization results of the plasma instrument treated membrane electrode (MnO2-P) and the original membrane electrode (MnO2) in Example 1 of the present invention; wherein Figure 1 a is the SEM image of MnO2-P; Figure 1 b and Figure 1 c are TEM images of MnO2-P and MnO2, respectively; Figure 1 d is the XRD pattern; Figure 1 is the specific surface area diagram; Figure 1 f is the pore size distribution diagram;

[0026] Figure 2 The electrochemical characterization results of the plasma instrument treated membrane electrode (MnO2-P) and the original membrane electrode (MnO2) in Example 1 of the present invention; wherein Figure 2 a is the ORR-LSV curve; Figure 2 b is the Tafel slope; Figure 2 c is the impedance diagram; Figure 2 d is the electrochemical active area diagram;

[0027] Figure 3 The cell performance characterization results of the plasma instrument treated membrane electrode (MnO2-P) and the original membrane electrode (MnO2) in Example 1 of the present invention; wherein Figure 3 a is the constant current discharge curve; Figure 3 b is the power density curve; Figure 3 c is a battery display diagram.

[0028] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] See also Figure 1-3 As shown, in this embodiment, a method for ultrafast processing of the surface microstructure of a large-scale membrane electrode is provided, comprising the following steps:

[0035] S1: Place the membrane electrode in a vacuum drying oven to remove moisture and ethanol inside the membrane electrode;

[0036] S2: self-cleaning in a plasma apparatus with a nitrogen atmosphere until the gas introduced into the chamber is entirely nitrogen;

[0037] S3: placing the membrane electrode into a plasma treatment apparatus with a nitrogen atmosphere for multiple treatments to obtain a treated membrane electrode.

[0038] In this embodiment, the vacuum drying oven in S1 has a vacuum degree of -1 to -3 MPa, a temperature of 60 to 80° C., and a drying time of 8 to 12 hours.

[0039] In this embodiment, the membrane electrode used in step S1 is a MnO2 membrane electrode.

[0040] In this embodiment, the cleaning power during self-cleaning in step S2 is 200 W, each cleaning time is 180 seconds, and the number of cleaning times is 3 times.

[0041] In this embodiment, in step S3, when a plasma treatment apparatus is used for treatment, the treatment power is 200 W, each treatment time is 15 to 30 minutes, the treatment time is 15-30min, and the number of treatments is 4 times.

[0042] In this embodiment, after each treatment in step S3, the membrane electrode needs to be rotated 90° before the next treatment.

[0043] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.

[0044] Embodiment 1: Provided is an ultrafast processing method for the surface microstructure of a large-scale membrane electrode, comprising the following steps:

[0045] S1: Place the membrane electrode in a vacuum drying oven and evacuate the vacuum to -3MPa. Set the temperature of the vacuum oven to 60°C for 12 hours to remove moisture and ethanol from the membrane electrode.

[0046] S2: Select high power (200W) for the plasma instrument, then open the nitrogen valve when the plasma instrument is working. Each cleaning time is 180s, and the cleaning times are 3 times. Until the next time the ion instrument works, the cavity emits bright red light without obvious stray light.

[0047] S3: Select high power (200W) for the plasma instrument, put the membrane electrode into the plasma instrument cavity, open the nitrogen valve, and process for 15 minutes each time. After processing the membrane electrode, rotate the membrane electrode 90° and put it into the plasma instrument to process the membrane electrode again. The number of processing times is 4 times.

[0048] S4: The treated membrane electrode and aluminum plate form an aluminum-air battery in 4M KOH solution.

[0049] The SEM image of the MnO2-P film electrode prepared in this example is as follows Figure 1 As shown in a, it can be seen from the figure that manganese dioxide exists in block form.

[0050] TEM images of MnO2-P film electrode and MnO2 film electrode Figure 1 b and Figure 1 As shown in Figure c, it can be seen from the yellow circle in the figure that after plasma treatment, the lattice fringes on the manganese dioxide interface gradually disappear, and Figure 1 The lattice fringes of the manganese dioxide interface without plasma treatment in c are clearly shown, proving that the crystallinity of the MnO2 film electrode is reduced after plasma treatment.

[0051] XRD tests were performed on MnO2-P membrane electrode and MnO2 membrane electrode. Figure 1 As shown in Figure d, it can be seen that the peak intensity of the MnO2-P film electrode is weaker than that of the MnO2 film electrode, which further proves that the crystallinity of MnO2 decreases after plasma treatment.

[0052] In the nitrogen adsorption and desorption tests of MnO2-P membrane electrode and MnO2 membrane electrode, Figure 1 As shown in Figures 1e and 1f, it can be seen that the MnO2-P film electrode exhibits a larger specific surface area and more mesopore distribution, which is mainly due to the plasma treatment that causes a large number of ion diffusion channels and grain boundaries to appear at the boundaries of manganese dioxide.

[0053] The MnO2-P membrane electrode and the MnO2 membrane electrode prepared in this example were subjected to electrochemical tests, and the ORR-LSV curves obtained were as follows: Figure 2 As shown in a, it can be seen from the figure that the half-wave potential of the MnO2-P film electrode in 0.1M KOH solution reaches 0.83V, which is close to 0.84V of commercial Pt / C and far exceeds 0.77V of the MnO2 film electrode. It can be seen that the MnO2-P film electrode prepared in this embodiment has excellent ORR catalytic activity.

[0054] ORR-LSV curve Figure 2 a is used to calculate the Tafel slope, and the result is as follows Figure 2 As shown in b, the Tafel slopes of MnO2-P membrane electrode, MnO2 membrane electrode and Pt / C are 82 mVdec, respectively. -1 、85mVdec -1 , and 115mVdec -1 , indicating that the membrane electrode treated by plasma has faster ORR reaction kinetics.

[0055] Electrochemical impedance spectroscopy also confirmed this trend. The smaller the semicircle diameter of the MnO2-P film electrode, the faster the charge transfer kinetics of the ORR process. Figure 2 c.

[0056] In the electrochemical active area test, Figure 2 As shown in d, the electrochemical active area value of the MnO2-P film electrode is 9.8 mF cm -2 , higher than the 9.4mFcm of commercial Pt / C -2 and 6.1mFcm of MnO2 membrane electrode -2 These data prove that after the plasma treatment, a large number of grain boundaries appear at the boundaries of manganese dioxide, exposing more active sites.

[0057] The MnO2-P membrane electrode and the MnO2 membrane electrode prepared in this example were assembled into an aluminum-air battery for testing. Figure 3 a Shown in 4M KOH solution and 5 mA cm -2 Under cross-current discharge at a current density of , the average voltage of the modified MnO2-P membrane electrode after working for 180 hours was about 1.4V, which was much higher than the 1.2V of the MnO2 membrane electrode and the 1.23V of commercial Pt / C.

[0058] Power density tests were performed on MnO2-P membrane electrode, MnO2 membrane electrode and commercial Pt / C. Figure 3 As shown in b, the power density of the MnO2-P membrane electrode reaches 110mWcm -2 Very close to the 113mWcm of commercial Pt / C -2 , much higher than the 78mWcm of MnO2 membrane electrode -2 .

[0059] Put the MnO2-P membrane electrode with a size of 110*70mm into a commercial aluminum-air battery mold, pour in 4MKOH solution, and the aluminum-air battery can drive 12W colored lights.

[0060] Embodiment 2: Provided is an ultrafast processing method for the surface microstructure of a large-scale membrane electrode, comprising the following steps:

[0061] S1: Place the membrane electrode in a vacuum drying oven and evacuate the vacuum to -2MPa. Set the temperature of the vacuum oven to 70°C for 12 hours to remove moisture and ethanol from the membrane electrode.

[0062] S2: Select high power (200W) for the plasma instrument, then open the nitrogen valve when the plasma instrument is working. Each cleaning time is 180s, and the cleaning times are 3 times. Until the next time the ion instrument works, the cavity emits bright red light without obvious stray light.

[0063] S3: Select high power (200W) for the plasma instrument, put the membrane electrode into the plasma instrument cavity, open the nitrogen valve, and process for 20 minutes each time. After processing the membrane electrode, rotate the membrane electrode 90° and put it into the plasma instrument to process the membrane electrode again. The number of processing times is 4 times.

[0064] S4: The treated membrane electrode and aluminum plate form an aluminum-air battery in 4M KOH solution.

[0065] Embodiment 3: Provided is an ultrafast processing method for the surface microstructure of a large-scale membrane electrode, comprising the following steps:

[0066] S1: Place the membrane electrode in a vacuum drying oven and evacuate the vacuum to -3MPa. Set the temperature of the vacuum oven to 80°C for 12 hours to remove moisture and ethanol from the membrane electrode.

[0067] S2: Select high power (200W) for the plasma instrument, then open the nitrogen valve when the plasma instrument is working. Each cleaning time is 180s, and the cleaning times are 3 times. Until the next time the ion instrument works, the cavity emits bright red light without obvious stray light.

[0068] S3: Select high power (200W) for the plasma instrument, put the membrane electrode into the plasma instrument cavity, open the nitrogen valve, and process for 30 minutes each time. After processing the membrane electrode, rotate the membrane electrode 90° and put it into the plasma instrument to process the membrane electrode again. The number of processing times is 4 times.

[0069] S4: The treated membrane electrode and aluminum plate form an aluminum-air battery in 4M KOH solution.

[0070] Embodiment 4: Provided is an ultrafast processing method for the surface microstructure of a large-scale membrane electrode, comprising the following steps:

[0071] S1: Place the membrane electrode in a vacuum drying oven and evacuate the vacuum to -2MPa. Set the temperature of the vacuum oven to 80°C for 8 hours to remove moisture and ethanol from the membrane electrode.

[0072] S2: Select high power (200W) for the plasma instrument, then open the nitrogen valve when the plasma instrument is working. Each cleaning time is 180s, and the cleaning times are 3 times. Until the next time the ion instrument works, the cavity emits bright red light without obvious stray light.

[0073] S3: Select high power (200W) for the plasma instrument, put the membrane electrode into the plasma instrument cavity, open the nitrogen valve, and process for 30 minutes each time. After processing the membrane electrode, rotate the membrane electrode 90° and put it into the plasma instrument to process the membrane electrode again. The number of processing times is 4 times.

[0074] S4: The treated membrane electrode and aluminum plate form an aluminum-air battery in 4M KOH solution.

[0075] Embodiment 5: Provided is an ultrafast processing method for the surface microstructure of a large-scale membrane electrode, comprising the following steps:

[0076] S1: Place the membrane electrode in a vacuum drying oven and evacuate the vacuum to -3MPa. Set the temperature of the vacuum oven to 60°C for 12 hours to remove moisture and ethanol from the membrane electrode.

[0077] S2: Select high power (200W) for the plasma instrument, then open the nitrogen valve when the plasma instrument is working. Each cleaning time is 180s, and the cleaning times are 3 times. Until the next time the ion instrument works, the cavity emits bright red light without obvious stray light.

[0078] S3: Select high power (200W) for the plasma instrument, put the membrane electrode into the plasma instrument cavity, open the nitrogen valve, and process for 30 minutes each time. After processing the membrane electrode, rotate the membrane electrode 90° and put it into the plasma instrument to process the membrane electrode again. The number of processing times is 4 times.

[0079] S4: The treated membrane electrode and aluminum plate form an aluminum-air battery in 4M KOH solution.

[0080] Test example: The MnO2-P membrane electrode and the MnO2 membrane electrode of Example 1 were crushed, and then the oxygen reduction activity test was carried out in 0.1M KOH: a rotating disk electrode device was used, a carbon rod was used as a counter electrode, a Hg / HgO electrode was used as a reference electrode, a platinum carbon electrode was used as a working electrode, and 0.1M KOH was used as an electrolyte. 5 mg of the target sample was dissolved in a solvent containing 40 μL 5% Nafion, 500 μL ultrapure water, and 500 μL isopropanol, 10 μL of electrode ink was dripped onto the platinum carbon electrode, dried naturally, and an electrochemical test was carried out at a rotation speed of 1600 rpm.

[0081] The MnO2-P membrane electrode and the MnO2 membrane electrode of Example 1 were assembled into an aluminum-air battery. 4MKOH was used as the electrolyte. The blue electric test system was used at a current density of 5 mA cm -2 Perform a discharge time test.

[0082] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. An ultrafast processing method for the surface microstructure of a large-scale membrane electrode, characterized in that: The following steps are involved: S1: Place the membrane electrode in a vacuum drying oven to remove moisture and ethanol inside the membrane electrode; S2: self-cleaning in a plasma apparatus with a nitrogen atmosphere until the gas introduced into the chamber is entirely nitrogen; S3: placing the membrane electrode into a plasma treatment apparatus with a nitrogen atmosphere for multiple treatments to obtain a treated membrane electrode.

2. The ultrafast processing method for the surface microstructure of a large-scale membrane electrode according to claim 1, characterized in that: The vacuum drying oven in S1 has a vacuum degree of -1 to -3 MPa, a temperature of 60 to 80°C, and a drying time of 8 to 12 hours.

3. The ultrafast processing method for the surface microstructure of a large-scale membrane electrode according to claim 1 is characterized in that: The membrane electrode used in step S1 is a MnO2 membrane electrode.

4. The ultrafast processing method for the surface microstructure of a large-scale membrane electrode according to claim 1, characterized in that: The cleaning power during self-cleaning in step S2 is 200 W, each cleaning time is 180 seconds, and the number of cleaning times is 3 times.

5. The ultrafast processing method for the surface microstructure of a large-scale membrane electrode according to claim 1, characterized in that: In step S3, when a plasma treatment apparatus is used for treatment, the treatment power is 200 W, each treatment time is 15 to 30 minutes, the treatment time is 15-30 minutes, and the number of treatments is 4 times.

6. The ultrafast processing method for the surface microstructure of a large-scale membrane electrode according to claim 1, characterized in that: After each treatment in step S3, the membrane electrode needs to be rotated 90° before the next treatment.

7. A membrane electrode, characterized in that: Obtained by the method according to any one of claims 1 to 6.

8. A membrane electrode according to claim 7, characterized in that: Applied to the positive electrode of aluminum-air battery or zinc-air battery.

9. An aluminum-air battery or zinc-air battery according to claim 8, characterized in that: The negative electrode of the aluminum-air battery or zinc-air battery is an aluminum plate or a zinc plate, respectively, and the electrolyte is a 4M KOH solution.